PHYSICAL-MATHEMATICAL MODEL OF SUBSTANCE REDISTRIBUTION BETWEEN THE CELL AND ITS HYPERTONIC SOLUTION ENVIRONMENT OF PENETRATING CRYOPROTECTANTS WITH RELEVANCE TO MEMBRANE POTENTIAL - Todrin, A.F.; Timofeyeva, O.V.; Smolyaninova, Ye.I.; Popivnenko, L.I.; O.I. Gordienko, O.I. (Cryoletters, 2020)
BACKGROUND: The redistribution of basic ions between the cell cytoplasm and its surrounding medium due to osmotic action affects transmembrane potential and plasma membrane integrity at all stages of low temperature preservation. OBJECTIVE: To develop a physical-mathematical model describing the redistribution of osmotically active solutes between the cell and its hypertonic solutions of penetrating cryoprotectants that enables the calculation of kinetic changes in cell volume, cryoprotectant and ion concentrations, as well as the cell transmembrane potential during cell equilibration with cryoprotectant solutions. MATERIALS AND METHODS: The study has modeled the mass transfer process of mouse oocytes upon exposure to 1.5 M DMSO and 1,2-Propanediol (1,2-PD) solutions. RESULTS: Equations for changes of the normalized volume as well as intracellular concentrations of DMSO, 1,2-PD, potassium, sodium, chlorine and transmembrane potential have been obtained in a dimensionless form. The membrane permeability coefficients for DMSO and 1,2-propanediol have been determined and compared with the data of Paynter et al (5). CONCLUSION: The study shows that the incorporation of transmembrane ion movement and electrical potential change in the mathematical model leads to lower values of mouse oocyte membrane permeability coefficients for water and cryoprotectants in comparison with data determined by the traditional model.
Keywords: mouse oocyte, water transport, ion transport, transmembrane electrical potential